Vascular anatomy of the anteromedial thigh flap. (September 2017) - Sun, Jeremy Mingfa; Chew, Khong Yik; Wong, Chin Ho; Goh, Terence Lin Hon
Abstract: Introduction: The anteromedial thigh flap (AMT) lies adjacent to the anterolateral thigh flap (ALT) area and can be used as a backup whenever the ALT is not feasible. Literature published on the AMT flap is limited, and the vascular anatomy of the AMT flap is not well understood. Clarification of the vascular anatomy will be useful for safe and efficient planning and raising of the AMT flap. Method: Fourteen cadaveric lower limbs were injected with latex dye and dissected to study the skin perforators larger than 0.5 mm in the anterolateral and anteromedial thigh. We demonstrate the application of the AMT flap in a clinical case where a combined ALT and AMT flap was used to reconstruct a tongue and floor of mouth defect post cancer resection. Results: Perforators that supplied the rectus femoris muscle and the overlying skin were present in all specimens and 12/14 (85.7%) specimens had rectus femoris branches (RFBs) originating from the descending branch of the lateral circumflex iliac artery. In total, 82.4% of AMT perforators are musculocutaneous (14/17 specimens), and they pierce the muscular fascia along a line drawn from the mid-inguinal point to the superomedial pole of the patella. The perforators congregate at the one-quarter mark and the midpoint of this line. This line is useful for the preoperative planning of the AMT flap. Conclusion: The anatomy of the RFB, which is critical in the blood supply of the AMT flap, is constant and predictable. The location of the perforators is predictable, which aids preoperative planning.